Sterilized intervention in emerging-market economies: Trends, costs, and risks - Robert Lavigne (Bank of Canada, 2008)
The author examines recent trends in sterilized intervention among emerging-market economies, to determine the size and extent of this policy in relation to earlier periods of heavy reserve accumulation. He then analyzes whether the domestic costs and risks of substantial and prolonged sterilization are beginning to manifest themselves. In particular, the author discusses the fiscal costs of sterilization and the recent increase in non-market-friendly sterilization methods, such as the rapid rise in reserve requirement ratios.
Keywords: F31; E52; O24; 330; Financial stability; Exchange rate regimes; International topics; Währungsreserven; Risiko; Inflationsrate; Wechselkursrisiko; Bubbles; Wirtschaftspolitik; Aufstrebende Märkte